(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
The increasing demand for construction materials necessitates the exploration of alternative and sustainable materials to supplement conventional resources. This study investigates the feasibility of partially replacing coarse aggregate in concrete with Jhama bricks, a type of over- burnt brick that is abundantly available in certain regions. The objective is to evaluate the mechanical and durability properties of concrete while promoting waste utilization and reducing dependency on natural aggregates. Theres earch involves preparing concrete mixtures with varying percentages (e.g., 10%, 20%, 30%) of Jhama brickaggregatesasa substitutefor conventionalcoarse aggregates. Experimental tests are conducted to assess key properties such as workability, compressive strength, tensile strength, and water absorption. Additionally, a comparative analysis is performed to evaluate the environmental and economic benefits of using Jhama brick aggregates. Preliminary results indicate that Jhama bricks exhibit sufficient mechanicalstrengthandbondingpropertiesto serve as a viable partial replacement. Concrete with a 20% substitution shows promising compressive strength, making it suitable for certain structural and non- structural applications. The study concludes with recommendations for practical implementation and furtherresearchtooptimizemixdesignandaddresslong- term performance.